Wind-Driven Mechanisms for the Variations of the Pacific Equatorial Undercurrent Based on Adjoint Sensitivity Analysis - Wang, Jin; Liu, Chuanyu; Wang, Xiaowei; Köhl, Armin; Lyu, Yilong; Li, Yuanlong; Wang, Fan (Frontiers in Marine Science, 2022)
The maintenance and variation of the Pacific Equatorial Undercurrent (EUC) are thought to be controlled by the zonal pressure gradient force (ZPGF). However, a recent study found that a large-scale circulation associated with Rossby waves can also lead to EUC variation, implying that the structures and timing of the influential winds and the underlying wind-driven mechanisms need to be revisited. Here, we use the adjoint-sensitivity method to obtain the crucial winds that can most efficiently influence EUC variations. The obtained adjoint sensitivities (denoting the sensitive winds) are confined to 15°S–15°N and exhibit a funnel-shaped pattern with high symmetry about the equator. The remote winds, which occur 4 to 11 months prior, can lead to EUC variations at the basin scale; in contrast, the near-term winds (occurring not earlier than 4 months) lead only to local EUC variations. Accordingly, we find that wind-initiated equatorial Kelvin waves, equatorial Rossby waves, and the reflected waves at both the western and eastern boundaries superimpose onto each other to result in EUC variations. Specifically, when the travel time is longer than 4 months, the waves can form a negative-positive-negative sea surface height anomaly (SSHA) pattern between 15°S and 15°N in the central-eastern tropical Pacific, indicating the joint effect of both types of waves; they also form a positive SSHA in the western equatorial Pacific, indicating the dominance of the Kelvin wave therein. These mechanisms are complementary to the canonical ZPGF mechanism, which provide a clear theoretical basis for EUC variation studies.